2022
DOI: 10.1021/acs.jchemed.1c01097
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Music: A Modern Accompaniment to NMR Pedagogy

Abstract: The NMR spectrometer is a commonly used spectroscopic instrument that records resonance frequencies of nuclei present in molecular systems. While the NMR frequencies fall within the radio frequency regime for a given molecular system, they are presented in terms of chemical shifts in the audio frequency regime, thereby having the versatility to be expressed as musical notes. Herein, we present a convenient methodology that enables conversion of NMR spectra into a collection of associated piano notes, and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the traditional teaching, the teacher's dominance is too strong, the learning situation under the teacher's guidance is overemphasized, and the students are already adults who can think and solve problems independently. A large number of psychological studies have shown that what adult students need most in the cognitive process is participation, and the best learning situation is cooperation and interaction [12][13][14]. In the teaching of practical courses in higher music colleges, teachers should change the teaching method of "teaching by heart" and mobilize students' awareness of active participation suggestions and solutions.…”
Section: Teaching Methods Design Of Practical Classmentioning
confidence: 99%
“…In the traditional teaching, the teacher's dominance is too strong, the learning situation under the teacher's guidance is overemphasized, and the students are already adults who can think and solve problems independently. A large number of psychological studies have shown that what adult students need most in the cognitive process is participation, and the best learning situation is cooperation and interaction [12][13][14]. In the teaching of practical courses in higher music colleges, teachers should change the teaching method of "teaching by heart" and mobilize students' awareness of active participation suggestions and solutions.…”
Section: Teaching Methods Design Of Practical Classmentioning
confidence: 99%
“…This feature not only offers deeper insights for users but also serves as a valuable educational tool. For example, with 13 C spectra that have a low SNR, the initial audio may be noisy. After an exponential apodization function is applied, the sound changes, enabling users to discern the difference and understand the effects of the preprocessing.…”
Section: Audification Methodologymentioning
confidence: 99%
“…Traditional pedagogy has relied heavily on visual aids, but auditory tools can bring forth a unique perspective that caters especially to visual or auditory learners. The study by Munukutla et al exemplifies this [13]. In their work, they transformed NMR spectra into sound, giving students a novel way to interact with and understand NMR data.…”
Section: Educational Echoes: Nmr In the Classroommentioning
confidence: 99%
“…It is not the first time that chemistry is taught with music. For example, Munukutla et al discovered a new NMR spectrometer learning method through mapping into music notes; 16 Vieira and Morais used analogies between chemistry and music to explain the kinetic-molecular theory, 17 and they also applied musical analogies to make topics from quantum model of the atom more accessible to middle school students. 18 In our work, we exposed the keen correlation between music objectivity and chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%